PENGARUH KEPEMIMPINAN, kOMPENSASI, MOTIVASI TERHADAP KINERJA PEGAWAI DINAS BINA MARGA JAWA TENGAH - Achmad Januandri Pratama, 11.05.51.0031 (Students Journal of Economic and Management, 2015)
This study analyzed on the influence of leadership, compensation and motivation on employee performance. Object of this research is the Highways Agency Java Tengah.Teknik sampling used was random sampling (random) amounted to 57 respondents in the sample data collection method using a questionnaire (questionnaire) by distributing a list of questions to the respondent in order to obtain information. The research objective was formulated to determine the effect of leadership, compensation and motivation on employee performance. The data were analyzed using factor analysis to test the validity of the question items, alpha chonbrach formula to test the reliability of each of the independent variables were tested by regression analysis. The results of the study are: (1) Leadership positive and significant impact on employee performance. (2) Compensation positive and significant impact on employee performance. (3) Motivation positive and significant impact on employee performance. Keywords: Leadership, Compensation, Motivation, and Performance